Analisis Representasi Gender Dalam Laporan Tahunan Perusahaan Manufaktur BUMN Terdaftar BEI Tahun 2016 - 2018 - Puspa Novita Sari (BUANA GENDER : Jurnal Studi Gender dan Anak, 2021)
This study aims to analyzeÂ the mission and social responsibility of state-owned companies in the manufacturing sector listed on IDX 2016-2018 is to reduce the problem of gender disparity in BUMN companies in the manufacturing sector by looking at photos published by companies in their annual reports published by related companies. To clarify each element of the evaluation, the research approach used is quantitative analysis to provide a summary of the proportions and qualitative descriptions. Krakatau Steel, Kimia Farma, and Semen Baturaja were the study artifacts used. Â It seems that several women are seen in the office based on the aspect of the position and rarely display the location in the sector. Considering that the research object is a state-owned enterprise engaged in production, this is understandable, so it is only natural that many activities in the field are carried out by male employees and seldom include female employees. In line with the representation of the aspect of the location, that dominates the representation of formal wear. Meanwhile, from the body language perspective, the position of men as speakers appears to be more dominant than women. Overall, it can be concluded that there was no equality between men and women in the gender representation shown in the annual reports of BUMN Manufacturing companies listed on IDX 2016-2018. The leader's figure shows more men, and the ability for women to lead the business is more limited than that of men